Referencing the body for mood state regulation: an examination of stress management using Dohsa-hou as a primary prevention program for nurses - Kazuaki Abe; Russell Sarwar Kabir; Yutaka Haramaki (Environmental and Occupational Health Practice, 2019)
Objectives: Stress management for human service professionals remains an international issue. Methods: We conducted a primary prevention program using Dohsa-hou designed to provide early-career nurses with an understanding of stress and physical relaxation skills that can be utilized to reduce negative and increase positive mood states. Results: A total of 56 nurses working at a general hospital in Japan participated in the program. As a result, negative mood states were significantly reduced at post-test from the intervention. Also, vigor as a positive mood state showed a marginal increase compared to pre-test. These findings were largely consistent with a previous study implementing Dohsa-hou movement tasks in a stress management program. Conclusions: Although there were some limitations, this study suggested that the stress management program using Dohsa-hou may be a useful approach for preventing burnout by promoting mood state regulation for nurses.